A STUDY ON CULTURAL INTEGRATION IN THE ENGLISH TEXTBOOKS FOR JUNIOR HIGH SCHOOLS - Sugirin Sugirim (LITERA, 2011)
The first phase of this two-year study aims at describing the teachers’ awareness to include culture in the teaching and learning process, what cultural aspects are included in the English textbooks used in a number of schools in the Province ofDIY and how the cultural elements are inserted in the books. The research data were obtained through a focus group discussion (FGD) attended by 20 English teachers from 5 regencies in the Province of DIY and from 7 English textbooks used by theseteachers. The data from the FGD were analyzed using qualitative data analysis, while the books were discerned using content analysis. The results of the analyses show (1) the teachers have inserted cultural elements in their teaching and learning process,following the explicit and implicit modes of insertion used in the textbooks; (2) the cultural elements in the books consist of knowledge, behaviors, and artifacts; and (3) there are 409 western cultural elements and 739 Indonesian ones, but they are notfollowed by adequate explanations to anticipate confusion and misunderstanding.